Perbandingan Profil Anestesi Kloroform dan Eter Ditinjau dari Waktu Induksi, Durasi, dan Efek Samping pada Tikus Putih - Haryanto Haryanto; Syaikhah Raihanah Herman; Abdi Mahdi; Zalva Atalya Rieuwpassa; Ashaja Syamsi (Inovasi Kesehatan Global, 2025)
This study aims to comparatively analyze the effects of two types of inhalation anesthetics, ether and chloroform, on Wistar rats, focusing on three main parameters: induction time, duration of anesthesia, and side effects. Selecting the appropriate anesthetic method is crucial in animal studies to ensure animal welfare and the validity of the results. Twenty male Wistar rats, with an average body weight of 200–250 grams and 10–12 weeks of age, were randomly divided into two treatment groups of 10 rats each. The first group was anesthetized using ether, while the second group was anesthetized using chloroform, with doses adjusted to achieve adequate levels of anesthesia. Measurements were made of the induction time, which is the interval from the start of anesthetic exposure until the loss of the pedal reflex; the duration of anesthesia, which is the length of time until the rat regains consciousness; and clinical observations of any side effects that appear, both during and after anesthesia. The results showed that the ether group had a relatively longer induction time than the chloroform group. However, ether provided a longer and more stable duration of anesthesia, with a better recovery rate. In contrast, chloroform produced a shorter induction time but was accompanied by a shorter duration of anesthesia and a higher risk of side effects, particularly liver dysfunction and respiratory depression. These findings reinforce previous reports that chloroform has significant potential toxicity, and its use in animal research should be limited. Based on these results, ether is recommended as a relatively safe inhalation anesthetic option for laboratory procedures in Wistar rats, although its use still requires strict supervision and appropriate handling procedures to ensure the safety of both researchers and experimental animals.